A 150 nm ultraviolet excitation volume on a porous silicon membrane for direct optical observation of DNA coil relaxation during capture into nanopores. Issue 1 (24th April 2017) - Yamazaki, Hirohito; Esashika, Keiko; Saiki, Toshiharu
Abstract: We report the first optical observation of DNA coil relaxation during capture into silicon nanopores, which was achieved using fluorescence microscopy with a 150 nm observation volume. Compared with our previous results, the gradual increase and steep decay of the fluorescence signal can be interpreted as the capture of the DNA molecule and its translocation through the nanopore, respectively. Furthermore, a longer dwell time was obtained when we used a nanoporous membrane with high porosity. From a numerical calculation of the electric field distribution in the vicinity of the nanopore, we concluded that a 'biased' electric field, as well as funneling of the field into surrounding nanopores, hinders DNA coil relaxation. Our result showed the capability of a UV excitation volume on a silicon membrane for observation of DNA capture into nanopores at a single-molecule level.